Approaches to synthesis of ([1,2,4]triazolo[1,5-c]quinazolin-2-yl)benzoic acids as potential anti-inflammators - N. I. Krasovska (Фармацевтичний журнал, 2022)
Despite their high efficacy NSAIDs have significant side effects due to non-selective inhibition of COX-1 and COX-2. Due to this, medical chemists still pay considerable attention to their design and synthesis, in particular the creation of hybrid molecules that combine in their structure a fragment with anti-inflammatory activity and the quinazoline heterocycle.